Seduced : Art & sex from antiquity to now - Wallace, Marina; Kemp, Martin; Bernstein, Joanne; Barbican Centre, London (London : Merrell Publishers Limited, 2007)
Dumas, Marlene ; Finoglia, Paolo ; Vecellio, Tiziano ; Peruzzi, Baldassare ; Barbieri, Giovanni Francesco ; Caracci, Agostino ; Romano, Giulio ; Zucchi, Jacopo ; Vouet, Simon ; Fragonard, Jean-Honoré ; et al.
Barbican Centre, London, 12 October 2007 - 27 January 2008
kunstcatalogus